Prospects for Sustainable Development of Cuba through Rational Use of Ecological Resources, Innovative Management and Strengthening Trade-Economic Cooperation with Russia (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Reviving Cuban-Russian trade cooperation offers significant potential for mutual benefit and strengthening both countries’ positions for sustainable development on the world stage. The aim of this study is to identify promising areas for bilateral trade growth and provide recommendations for developing ecological and economic collaboration. The objectives include: 1) analyzing the stages of Cuba’s foreign trade development in relation to its economy, population growth, HDI dynamics, and the evolution of its trade system; 2) identifying promising directions based on historical experience and current realities; and 3) assessing key areas of cooperation to overcome barriers. Both quantitative (statistical analysis, graphs, tables) and qualitative methods (legislative interpretation, expert opinions) are used. Special attention is given to the role of small and medium-sized enterprises in Cuba’s economy and the challenges of implementing “change management” approaches to modernize public administration and industry. The results show that Cuba faces limited energy resources, food shortages, outdated technologies, import dependence, labor shortages, and social inequality. Addressing these challenges requires systemic measures: economic modernization, development of ecological education and science, and increased efficiency in both the public and private sectors. The experience of the “Special Period” underscores the importance of rational use of biodiversity and ecological resources and autonomous agriculture. Cuban-Russian cooperation is promising in energy, biotechnology, ecological management, “change management”, tourism, and logistics. International investment in solar power plants, agro-industrial complexes, and infrastructure can accelerate Cuba’s sustainable development. Cuba as a miltidisciplinary hub, in turn, offers access to Latin American markets and opportunities for collaborative projects, etc. Joint efforts are essential for achieving the UN Sustainable Development Goals-2030. Strengthening trade, economic, and ecological ties should be based on principles of sustainability, innovative management, and intercultural cooperation, which will enhance competitiveness and contribute to a fairer and more multipolar world.
Keywords: Cuba; trade development; eco-innovations; green technologies